BULK RNA-SEQUENCING OF BLOOD INFORMS MOLECULAR DIAGNOSES IN VERY EARLY ONSET INFLAMMATORY BOWEL DISEASE. (26th January 2023) - Collen, Lauren; Field, Michael; Eran, Alal; Mitsialis, Vanessa; Barends, Jared; Saccocia, Gwen; Bresnahan, Mairead; Yang, Jessica; Buijsen, Fleur; Combs, Abigail; Tuthill, Margaret; Bearup, Richelle; et al.
Abstract: BACKGROUND: Very early onset inflammatory bowel disease (VEOIBD) is defined as disease onset prior to age 6. VEOIBD is monogenic in >5% of cases; however, in the remaining cases, molecular basis of disease is unknown. We aimed to utilize bulk RNA-seq of blood to 1) define transcriptional signatures in established monogenic IBD and 2) to inform novel molecular diagnoses. METHODS: We sequenced the transcriptomes of 115 whole blood samples, comprising patients with VEOIBD of a known monogenic cause (n=35), VEOIBD without a known monogenic cause (n=70), and healthy controls (n=10). We focused on genes whose normalized expression was at least 5 standard deviations away from the population mean in at least one sample. We comprehensively characterized clinical phenotypes, to assess concordance with known pathway and gene function, and compared to whole exome sequencing data where available. We interrogated Bayesian IBD networks to assess for enrichment of genes of interest. RESULTS: First, we report on a novel transcriptional signature shared by two patients with VEOIBD secondary to X-linked agammaglobulinemia (pathogenic BTK mutations). The signature is defined by under-expression of CXCR5 and FCRL5 (Fig 1) and suggests reduced transcripts secondary to B-cell depletion or novel BTK -dependent mechanisms of gene transcription. Second, we report on three novel candidate VEOIBD genes identified through our approach: MSN, SLC39A4, and BTN3A2 (Fig 2). MSN expression was below threshold in one patient with VEOIBD complicated by fistulae, recurrent infections, and death from pneumonia at age 62. Review of his exome revealed a novel loss of function mutation in MSN . MSN encodes moesin, an actin cytoskeleton modulator, which regulates lymphocyte migration and adhesion. Mutations in MSN are associated with X-linked moesin-associated immunodeficiency, which was first reported in a patient with IBD this year. SLC39A4, which encodes an intestinal zinc transporter, was below threshold in two patients. Mutations in SLC39A4 are associated with acrodermatitis enteropathica, characterized by dermatitis and diarrhea. One patient has VEOIBD with dermatitis; the second has VEOIBD complicated by toxic megacolon and colectomy. Coding mutations in SLC39A4 have not been identified. Further molecular assessment of zinc transporter function is underway. Lastly, BTN3A2 expression was below threshold in two patients with infantile-onset IBD. BTN3A2 plays a role in T cell receptor interactions and NF-KB signaling. Bayesian IBD networks, built from independent cohorts, revealed BTN3A2 and SLC39A4 subnetworks to be enriched in predicted key driver genes of inflammation, further supporting these genes' potential disease association. CONCLUSIONS: Bulk RNA-seq in blood can be used as a diagnostic tool to aid in identifying novel molecular pathways and monogenic diagnoses in VEOIBD.